Gender and Climate change Action Plan for Mali - Chioma, Ogwuike; Dossou-Yovo. E. R (2024)
"Mali is a landlocked, Sahelian country in West Africa. The Climate Change Vulnerability Index produced by ND-GAIN in 2023 ranked Mali as 176th of the 181 most at-risk countries in the world1. It is the 9th most vulnerable country and the 43rd least ready country to address climate change effects. Mali is ranked 155th out of the 170 countries included in the 2021 UNDP Gender Inequality Index (UNDP,2021). Mali is home to the inner delta of the Niger River that runs through nine countries in the region. The country is influenced by the Inter-Tropical Conversion Zone (ITCZ) which is, creating winds from Ocean and the winds from the Sahara region that are more dusty and warmer. The country is already experiencing the climate change impacts of droughts, floods, storms, strong winds, and increased temperature variability. These events can have a devastating impact on crop yields, livestock production, and food security. Available evidence indicates that climate change in Mali is likely to be characterized by increased local temperatures, greater rainfall variability, and more intense extreme weather events. Gender dynamics are integral to the climate change discourse in Mali, as men, women, and youth play distinctly disproportionate roles in agriculture. They also face varying degrees of challenges in accessing critical production resources such as land, water, and credit. Women, who constitute over 50% of the agricultural labor force, are primarily responsible for food production. However, gender inequality persists despite previous global, regional, and national commitments to uphold and advance women’s rights. This Action Plan seeks to address the gender dimensions of climate change within the agricultural sector and is centered around four key objectives, including: (i) increase women and youth's access to land, water, and credit. (ii) improve knowledge and skills of the various gender groups (women, men, and youths) in climate change adaptation with a determined effort to narrow down existing gender gaps among the groups. (iii) strengthen women's participation in decision-making and policymaking related to climate change. (iv) promote the use of gender-sensitive indicators to monitor and evaluate the climate change related programs. The plan is expected to have several benefits, including: I. increased food security and nutrition for women and their families. II. improved livelihoods for men, women, and youths. III. increased resilience to climate change. IV. increased gender equality in the agricultural sector.